The Ins and Outs of Rural Teachers: Who Are Atheists, Agnostics, and Freethinkers - Aimee Howley; Craig Howley; Marged Dudek (Journal of Research in Rural Education, 2016)
Perhaps the most maligned group of people in the United States, atheists and other nonbelievers (e.g., agnostics and freethinkers) reside everywhere and are employed in every fi eld. Disclosure of nonbelief generally imposes costs, such as alienation from family and associates or even loss of employment. As a result, nonbelievers often disguise their views about the existence of a god. This article reports fi ndings from a qualitative study based on interviews with 24 nonbelieving teachers in rural schools across the United States, illuminating the ways these teachers position themselves professionally and intellectually in communities with relative homogeneity of cultural beliefs and practices. Using a person-oriented mode of analysis, the study identifi ed four types of rural non-believing teachers: community insiders or outsiders who disclosed or did not disclose their nonbelief. Their decisions about self-disclosure intersected with community attachment, pedagogical judgments, and regionality, but common across the types was teachers' determination to cultivate their students' thinking. Most teachers believed that intellectual skepticism did not require religious skepticism. This perspective, however, sometimes confl icted with local expectations that public schools inculcate Christian beliefs.